Effect of calcium content on the microstructure, hardness and in-vitro corrosion behavior of biodegradable Mg-Ca binary alloy - Harandi,Shervin Eslami (2013)
Effect of calcium addition on microstructure, hardness value and corrosion behavior of five different Mg-xCa binary alloys (x = 0.7, 1, 2, 3, 4 wt. (%)) was investigated. Notable refinement in microstructure of the alloy occurred with increasing calcium content. In addition, more uniform distribution of Mg2Ca phase was observed in a-Mg matrix resulted in an increase in hardness value. The in-vitro corrosion examination using Kokubo simulated body fluid showed that the addition of calcium shifted the fluid pH value to a higher level similar to those found in pure commercial Mg. The high pH value amplified the formation and growth of bone-like apatite. Higher percentage of Ca resulted in needle-shaped growth of the apatite. Electrochemical measurements in the same solution revealed that increasing Ca content led to higher corrosion rates due to the formation of more cathodic Mg2Ca precipitate in the microstructure. The results therefore suggested that Mg-0.7Ca with the minimum amount of Mg2Ca is a good candidate for bio-implant applications.